Methodological Peculiarities of the Usage of Stretching Techniques in the Process of Flexibility Development - Oksana Romaniuk; Bohdan Zadvornyi (Lesya Ukrainka Volyn National University, 2017)
The article is devoted to theoretical and methodological substantiations of the body flexibility development practically applying the stretching techniques. It was generalized scientific data on the organization and methodological features of stretching exercises. Semantic content and structural componential model of stretching usage in the process of flexibility development and the estimation of the changes of this characteristic according to the age were carried out. In particular, some parameters were highlighted especially which allow to recommend that methodology both for individual and group usage were analyzed. Besides, it was analyzed the diversity of physiological mechanism of the influence of stretching on human body, especially it was singled out the effect on mental and physical spheres of human being. The generalized scientific data on the theoretical and practical aspects of flexibility development with the help of stretching techniques indicate the priority of usage of this method in many types of physical activities irrespective of the scope of its practical application.